2015
DOI: 10.5966/sctm.2014-0027erratum
|View full text |Cite
|
Sign up to set email alerts
|

Human Perivascular Stem Cell-Based Bone Graft Substitute Induces Rat Spinal Fusion

Abstract: Adipose tissue is an attractive source of mesenchymal stem cells (MSCs) because of its abundance and accessibility. We have previously defined a population of native MSCs termed perivascular stem cells (PSCs), purified from diverse human tissues, including adipose tissue. Human PSCs (hPSCs) are a bipartite cell population composed of pericytes (CD146+CD342CD452) and adventitial cells (CD1462CD34+ CD452), isolated by fluorescence-activated cell sorting and with properties identical to those of culture identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 73 publications
5
39
0
Order By: Relevance
“…This is in line with the literature claiming that the quintessential MSC derives from the perivascular niche (Crisan et al, 2008). Their ability to contribute to osteogenic repair has been validated in four distinct models: rat spinal fusion (Chung et al, 2014), murine muscle pouch, murine femoral segmental defect and rat calvarial defect, the latter two of which will not display self-healing due to their critical size (James et al, 2012b). However, although perivascular cells are capable of differentiation into osteoblasts and osteocytes, the majority of neo-bone is of host origin, suggesting that they contribute to bone formation via the secretion of trophic factors (Chung et al, 2014).…”
Section: Bone Fat and Cartilagesupporting
confidence: 86%
See 3 more Smart Citations
“…This is in line with the literature claiming that the quintessential MSC derives from the perivascular niche (Crisan et al, 2008). Their ability to contribute to osteogenic repair has been validated in four distinct models: rat spinal fusion (Chung et al, 2014), murine muscle pouch, murine femoral segmental defect and rat calvarial defect, the latter two of which will not display self-healing due to their critical size (James et al, 2012b). However, although perivascular cells are capable of differentiation into osteoblasts and osteocytes, the majority of neo-bone is of host origin, suggesting that they contribute to bone formation via the secretion of trophic factors (Chung et al, 2014).…”
Section: Bone Fat and Cartilagesupporting
confidence: 86%
“…Moreover, the progenitor cell potential and secretion of pro-repair factors by pericytes means that their recruitment to sites of injury is highly desirable. Previously, sources of MSCs for the regeneration of mesenchymal tissue have included the bone marrow, adipose tissue and the stromal vascular fraction (SVF) of adipose tissue (Chung et al, 2014).…”
Section: Contribution Of Mscs and Pericytes To Ex Vivo Tissue Engineementioning
confidence: 99%
See 2 more Smart Citations
“…prospectively identified human vascular pericytes from multiple human organs based on the expression of CD146 (Mel-CAM), nerve/glial antigen 2 (NG2), and platelet-derived growth factor receptor-β (PDGFR-β), and demonstrated that pericytes are one of the origins of mesenchymal stem cells (MSCs). Pericytes show regenerative potential in injured skeletal muscle,9, 10 ischemic heart,11, 12 bone,13, 14 adipose tissue, 15 and dental pulp 16 ; therefore, they are regarded as a local reservoir of regenerative cells 17, 18. In tissue fibrosis, pericytes have a pathological role in which they proliferate and differentiate into collagen-I–producing myofibroblasts 19, 20.…”
mentioning
confidence: 99%